MSCT of huge abdominopelvic masses in female: a pictorial illustration - Hassan, Radhiana; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Abdullah, Suhaiza (2011)
Introduction: The differential diagnoses for huge abdominopelvic masses in female are extensive. Many of these masses arise from the reproductive organs such as uterus, cervix and ovaries. Majority represents the commonly encountered entities such as uterine fibroid, dermoid tumour, ovarian cyst and ovarian cancer. However, some of the masses may arise from other organs such as the gastrointestinal system, urinary system, adjacent soft tissue, retroperitoneum or from metastasis. With large mass, it is a challenge for radiologists to determine the site of origin and to differentiate between these tumours. Case series We retrospectively reviewed MSCT performed for huge abdominopelvic masses. The CT findings were correlated with intra-operative findings and final HPE report. This pictorial illustration emphasize on differential diagnosis of huge abdominopelvic masses. Conclusion Familiarity with clinico-pathologic and imaging features is important and helpful for correct image interpretation of common and uncommon abdominopelvic masses.